Racial Differences in Postoperative Opioid Prescribing Practices in Spine Surgical Patients. Issue 3 (16th March 2023) - Letchuman, Vijay; He, Liangliang; Mummaneni, Praveen V.; Agarwal, Nitin; Campbell, Liam J.; Shabani, Saman; Chan, Andrew K.; Abrecht, Christopher R.; Miller, Catherine; Sankaran, Sujatha; Rambachan, Aksharananda; Croci, Rhiannon; et al.
Abstract : BACKGROUND: As the opioid epidemic accelerates in the United States, numerous sociodemographic factors have been implicated its development and are, furthermore, a driving factor of the disparities in postoperative pain management. Recent studies have suggested potential associations between the influence of race and ethnicity on pain perception but also the presence of unconscious biases in the treatment of pain in minority patients. OBJECTIVE: To characterize the perioperative opioid requirements across racial groups after spine surgery. METHODS: A retrospective, observational study of 1944 opioid-naive adult patients undergoing a neurosurgical spine procedure, from June 2012 to December 2019, was performed at a large, quaternary care institute. Postoperative inpatient and outpatient opioid usage was measured by oral morphine equivalents, across various racial groups. RESULTS: Case characteristics were similar between racial groups. In the postoperative period, White patients had shorter lengths of stay compared with Black and Asian patients ( P < .05). Asian patients used lower postoperative inpatient opioid doses in comparison with White patients ( P < .001). White patients were discharged with significantly higher doses of opioids compared with Black patients ( P < .01); however, they were less likely to be readmitted within 30 days of discharge ( P < .01). CONCLUSION: In a large cohort of opioid-naive postoperative neurosurgical patients, this study demonstrates higher inpatient and outpatient postoperative opioid usage among White patients. Increasing physician awareness to the effect of race on inpatient and outpatient pain management would allow for a modified opioid prescribing practice that ensures limited yet effective opioid dosages void of implicit biases.